Zdravljenje avtoimunske hemolitične anemije z rituksimabom - Mlakar, Uroš (Zdravniški vestnik, 2004)
Background. Autoimmune haemolytic anaemia (AIHA) is characterised by the presence of autoantibodies directed against autologous erythrocytes. Dependingon temperature at which they are active AIHA is classified as AIHA due to warm or cold-reacting antibodies. Glucocorticoids are the mainstay of treatment for patients with AIHA due to warm autoantibodies. If haemolysis cannot be controlled by a low dose of glucocorticoids, then splenectomy is indicated. Immunosuppressive therapy with cytotoxic drugs is reserved for those patients who fail to respond to glucocorticoids and splenectomy or for those who are poor surgical risks. Cold agglutinin disease is a chronic haemolytic anaemia that is refractory to the usual treatments for haemolytic anaemia mediated by a warm-reactive antibody. Innovative approaches are neededfor patients with AIHA that does not respond to conventional treatment. Rituximab is a monoclonal antibody against CD20 antigens on B cells. It has been introduced for the treatment of B-cell lymphomas. The successful treatments of refractory idiopathic cold agglutinin disease with rituximab were reported recently. Methods and results. In this paper we present three cases of chronic AIHA refractory to immunosuppressive treatment. Two patients were with cold agglutinin disease secondary to lymhoplasmacytic lymphoma. One of two had mixed cold and warm-reacting antibodies. The third case was with idiopathic AIHA due to warm-reacting antibodies. Treatment of secondary cold agglutinin disease with rituximab was unsuccessfully, while in patient with idiopathic warm-reacting AIHA remission was achieved. The patient has been without anaemia and without laboratory signs of hemolysis more then 10 months.Conclusions. Treatment with rituximab appears promising for idiopathic refractory AIHA. We suggest that combination of rituximab with chemotherapy insecondary cold agglutinin disease due to lymphoid neoplasm is better choice than rituximab alone.
Keywords: Anemia, Hemolytic, Autoimmune; Anemija hemolitična, avtoimunska; Antibodies, Monoclonal; Antigeni, CD20; Antigens, Cd20; Autoantibodies; Avtoprotitelesa; Drug Therapy; Limfom malih limfocitov; Lymphoma, Small Lymphocytic; Middle Age; Protitelesa monoklonska; Srednja leta; Therapeutic Use; Treatment Outcome; Zdravljenje, izid